Multi-spacecraft study of the solar wind at solar minimum: Dependence on latitude and transient outflows - Laker,R; Horbury,TS; Bale,SD; Matteini,L; Woolley,T; Woodham,LD; Stawarz,JE; Davies,EE; Eastwood,JP; Owens,MJ; O'Brien,H; Evans,V; et al. (Astronomy and Astrophysics: a European journal, 2021)
Context. The recent launches of Parker Solar Probe, Solar Orbiter (SO), and BepiColombo, along with several older spacecraft, have provided the opportunity to study the solar wind at multiple latitudes and distances from the Sun simultaneously.Aims. We take advantage of this unique spacecraft constellation, along with low solar activity across two solar rotations between May and July 2020, to investigate how the solar wind structure, including the heliospheric current sheet (HCS), varies with latitude.Methods. We visualise the sector structure of the inner heliosphere by ballistically mapping the polarity and solar wind speed from several spacecraft onto the Sun’s source surface. We then assess the HCS morphology and orientation with the in situ data and compare this with a predicted HCS shape.Results. We resolve ripples in the HCS on scales of a few degrees in longitude and latitude, finding that the local orientations of sector boundaries were broadly consistent with the shape of the HCS but were steepened with respect to a modelled HCS at the Sun. We investigate how several CIRs varied with latitude, finding evidence for the compression region affecting slow solar wind outside the latitude extent of the faster stream. We also identified several transient structures associated with HCS crossings and speculate that one such transient may have disrupted the local HCS orientation up to five days after its passage.Conclusions. We have shown that the solar wind structure varies significantly with latitude, with this constellation providing context for solar wind measurements that would not be possible with a single spacecraft. These measurements provide an accurate representation of the solar wind within ±10° latitude, which could be used as a more rigorous constraint on solar wind models and space weather predictions. In the future, this range of latitudes will increase as SO’s orbit becomes more inclined.